Implementasi Budaya Kerja Organisasi dalam Menciptakan Lingkungan Kerja Kondusif di PT Ganesa Mitra Edutama - Elsa Oktavia Dilla; Agnesia Natania Lumiu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
A conducive work environment is one of the essential factors in supporting employee performance and comfort. PT. Ganesa Mitra Edutama, a company operating in the education and service sector, faces challenges in consistently implementing organizational work culture to create a harmonious, comfortable, and productive work environment. The issues encountered are related to internal communication patterns, the implementation of work values, and the alignment of employee work behavior with the prevailing organizational culture. This study aims to examine the implementation of organizational work culture in creating a conducive work environment at PT. Ganesa Mitra Edutama and to formulate improvement strategies for organizational culture that can be implemented by the company.This study employs a qualitative descriptive approach, with informants selected through purposive sampling, focusing on key persons who possess an in-depth understanding of the company’s work culture and work environment. Data were collected through in-depth interviews, observation, and documentation. The analysis is based on the work environment theory proposed by Budiasa (2021:43), which includes indicators of physical and non-physical work environment, such as work relationships, communication, comfort, work atmosphere, and leadership support.The results indicate the implementation of organizational work culture at PT. Ganesa Mitra Edutama has been carried out fairly well, particularly in fostering harmonious work relationships and a familial work atmosphere. However, several aspects still require improvement, especially in the consistency of applying organizational work culture values, internal communication patterns, and strengthening the role of leadership as a role model for organizational culture. The proposed organizational culture improvement strategies include reinforcing work culture values through continuous socialization, enhancing internal communication quality, and creating a more participative work system to support the establishment of a more conducive work environment.